The Dynamics of Democratization : Elites, Civil Soceity and the Transition Process - Gill, Graeme (Palgrave Macmillan, 2000)
One of the most significant developments in the last three decades of the twentieth century was the fall of many authoritarian regimes and their replacement by governments claiming democratic credentials. Althought the most spectacular instance of this was the collapse of communism, epitomized by the fall of the Berlin Wall in 1989, it has occured in a much wider range of countries , from Spain and Greece to Uruguay and South Korea.